2016
DOI: 10.1016/j.scitotenv.2016.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor urban nanomaterials: The emergence of a new, integrated, and critical field of study

Abstract: Engineered nanomaterials (ENMs) are currently widely incorporated in the outdoor urban environmental fabric and numerous new applications and products containing ENMs are expected in the future. As has been shown repeatedly, products containing ENMs have the potential, at some point in their lifetime, to release ENMs into their surrounding environment. However, the expanding body in environmental nanomaterial research has not yet shifted toward ENMs in the context of the complex outdoor urban environment. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 138 publications
(180 reference statements)
1
44
1
Order By: Relevance
“…Instead, we measured a great deal of variation across all of the ponds and found, similar to Baalousha et al. (), that even ponds surrounded by significant buffers of undeveloped land were receiving measurable quantities of urban pollutants via direct deposition.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Instead, we measured a great deal of variation across all of the ponds and found, similar to Baalousha et al. (), that even ponds surrounded by significant buffers of undeveloped land were receiving measurable quantities of urban pollutants via direct deposition.…”
Section: Discussionsupporting
confidence: 76%
“…of substrates (inorganic N and DOC) nor the concentrations of stressors (metals) were consistently related to surrounding land use across ponds. Instead, we measured a great deal of variation across all of the ponds and found, similar to Baalousha et al (2016), that even ponds surrounded by significant buffers of undeveloped land were receiving measurable quantities of urban pollutants via direct deposition.…”
Section: Discussionmentioning
confidence: 55%
“…From this, one must tie these insights together to start to gain a more holistic sense of all classes of nanomaterial-Earth system scenarios. For example, accelerating urbanization will affect nanomaterial-mediated processes, with localized consequences to environmental and human health in the built environment (102). Evolution of energy production systems will drive changes in the sources and distribution of nanomaterials, with global-scale consequences.…”
Section: New Opportunities For Researchmentioning
confidence: 99%
“…Nanomaterial transformation in fresh water systems is an active field of research [216]. Nanoparticle assessments have concluded that fine particulate matter occurs in a variety of water sources [217][218][219][220][221], so its impact on irrigation water, accumulation in soil, and potential for crop uptake is of paramount significance.…”
Section: Engineered Nanomaterialsmentioning
confidence: 99%